2020
DOI: 10.9734/jalsi/2020/v23i530161
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Assessment of Antiplasmodial Activity and Acute Oral Toxicity of Dissotis rotundifolia Extracts and Fractions on Plasmodium falciparum Strains

Abstract: Aim: Dissotis rotundifolia were selected after an ethnopharmacological survey conducted on plants used traditionally for malaria treatment in South Benin, with the aim of discovering new natural active extracts against malaria parasites. Place and Duration of Study: Laboratory of Biochemistry and Bioactive Natural Substances, University of Abomey-Calavi (Benin)/ Laboratory of Infectious Vector Borne Diseases, Regional Institute of Public Health (Benin)/ Laboratoire d’Histologie, de Cytogénétique et d’Emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, a study conducted in southern Benin has reported that medicinal plant species such as Dissotis rotundifolia, Ehretia cymosa Thonn, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl are commonly used by populations for malaria treatment [10]. Furthermore, the use of these medicinal plants as malaria remedies has been validated by in vitro evaluation of their antiplasmodial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study conducted in southern Benin has reported that medicinal plant species such as Dissotis rotundifolia, Ehretia cymosa Thonn, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl are commonly used by populations for malaria treatment [10]. Furthermore, the use of these medicinal plants as malaria remedies has been validated by in vitro evaluation of their antiplasmodial activity [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the drug-exposed and unexposed parasites were genotyped using Msp1 and Msp2 markers. 4) Beninese medicinal plants including Dissotis rotundifolia, Hibiscus surattensis L., Cola millenii K. Shum, and Costus afer Ker Gawl, which have been previously found to be active against asexual P. falciparum [11][12][13][14], were used. Furthermore, the crude extract of the antimalarial plant species Ehretia cymosa Thonn and a compound encoded CpE2, previously extracted from this plant (unpublished data), was screened.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation